Revolutionizing Traffic Light Systems: AI Implementation For Efficiency And Safety - Aditya, Nopriansah Dwi; Pratama, Ricky; Piransyah, M. Rafly; Juita, Nelya (Innovative: Journal Of Social Science Research, 2025)
Traffic light systems play a crucial role in modern transportation management by improving traffic efficiency and road safety. However, challenges arise, particularly in adapting to dynamic traffic conditions in developing countries like Indonesia. This article discusses how the implementation of Artificial Intelligence (AI) can transform traffic light systems into more adaptive and responsive infrastructures. Studies indicate that AI-based technologies can reduce congestion by up to 30%, decrease greenhouse gas emissions, and enhance intersection safety. The article also examines the challenges of implementing this technology in Indonesia and provides strategic recommendations for its success.